PERISTIWA CAMPUR KODE DALAM CERAMAH K.H. ANWAR ZAHID PADA ACARA BERSIH DESA DI LAMPUNG - Auni Faridah, Emi Auni Faridah; Eko Retnosari, S.S., M.Pd., Ira (Buana Bastra, 2019)
Code mixing is a theory that studies about the mixing of two or more languages. Codemixing can be defined as the use of two or more language codes by speakers, which one of thecodes used is only a word fragment. The object of this research was speech video by K.H.Anwar Zahid and the focus of the study in this research was the form, type, and function ofcode mixing in the speech of K.H. Anwar Zahid in the event of bersih desa in Lampung. Thereason to choose people of Tunggal Jaya village, district of Banjar Agung, regency of TulangBawang, city of Lampung, because 80% of the people were transmigrant. Hence, it was easierto find the code mixed used in Lampung.The method used in this research was descriptivemethod by using qualitative research approach. To collect the data, in this research usedlisten and matching method, it was listening to the language used by K.H. Anwar Zahid fromthe video and match of this video. Thus, the data analysis techniques in this research wascollecting data, finding the form, type, and function of code mixing, classifying, reducing,describing, and interpreting it. Based on the results of the study that had been done, therewere five codes mixing found and those were: words, phrases, baster, repetition words, andclauses that used in every speech. Most of data was found in this research was a code mixingin the form of words. The kind of code mixing that had been found in this research were: hada function as repetition, insertion of the sentence, and often found as the function ofspecification conversation